The Politics of Cancel Culture: Origins, Identity, and Prognostications of Cancel Culture in South Africa - Dunlop, John Anthony Blackadder (University of the Witwatersrand, Johannesburg, 2023)
In this Research essay, I identify five socio-political developments, trends, and or features which characterize the relationship between Cancel Culture and South Africa. Firstly, because of Cancel Culture’s origins and notoriety, the concept was moulded in the United States and, therefore, a modern liberal device. Secondly, because of its roots Cancel Culture is also founded upon ideas around identity and woke politics. Thirdly, South Africa’s employment of Cancel Culture is justified within the country’s common and most troublesome socio-political struggles, which include issues with racism, decolonization, sexual assault, and gender-based violence. Fourthly, South African Cancel Culture, is ideologically and politically non-partisan, as there doesn’t seem to be an overload of opposition, claim and dismissal for the concept. Lastly, South Africa’s right-wing conservatives and far-right factions are not as hyper-critical of Cancel Culture, and their discontent and critiques of the socio-political phenomenon are not well published when compared to the Western World. This essay argues and predicts that: firstly, Cancel Culture will not take an extensive period before it becomes a household name, and more cases or examples will follow. Secondly, Cancel Culture’s social media presence will escalate, which will allow for further development and evolution of the concept. Thirdly, Cancel Culture will become a prominent fixture and component among South Africa’s various Universities. There will be an upsurge in self-censorship and political correctness amongst South African citizens to prevent attempted cancellations. South African liberals and far-left advocates will continue to be Cancel Culture’s principal protagonists and perpetuators. Following that, right-wing, conservative, and far-right South Africans will aim to retort and resist the rise of Cancel Culture. I contend that parallel to the United States, Cancel Culture will continue to be an ineffective feature of South Africa’s contemporary socio-political environment. Lastly, because of Cancel Culture’s online presence and notoriety, the concept will have a dramatic increase in academic enquiry, research, and literature.
A research report submitted in partial fulfilment of the requirements for the Degree of Masters of Arts in Political Studies, School of Social Sciences, in the Faculty of Humanities at the University of the Witwatersrand. Johannesburg, in 2023.
Keywords: Politics; Cancel culture; Identity; South Africa; UCTD